CBL controls a tyrosine kinase network involving AXL, SYK and LYN in nilotinib‐resistant chronic myeloid leukaemia. Issue 1 (4th June 2015) - Gioia, Romain; Trégoat, Claire; Dumas, Pierre‐Yves; Lagarde, Valérie; Prouzet‐Mauléon, Valérie; Desplat, Vanessa; Sirvent, Audrey; Praloran, Vincent; Lippert, Eric; Villacreces, Arnaud; Leconet, Wilhem; Robert, Bruno; et al.
Abstract A tyrosine kinase network composed of the TAM receptor AXL and the cytoplasmic kinases LYN and SYK is involved in nilotinib‐resistance of chronic myeloid leukaemia (CML) cells. Here, we show that the E3‐ubiquitin ligase CBL down‐regulation occurring during prolonged drug treatment plays a critical role in this process. Depletion of CBL in K562 cells increases AXL and LYN protein levels, promoting cell resistance to nilotinib. Conversely, forced expression of CBL in nilotinib‐resistant K562 cells (K562‐rn) dramatically reduces AXL and LYN expression and resensitizes K562‐rn cells to nilotinib. A similar mechanism was found to operate in primary CML CD34+ cells. Mechanistically, the E3‐ligase CBL counteracts AXL/SYK signalling, promoting LYN transcription by controlling AXL protein stability. Surprisingly, the role of AXL in resistance was independent of its ligand GAS6 binding and its TK activity, in accordance with a scaffold activity for this receptor being involved in this cellular process. Collectively, our results demonstrate a pivotal role for CBL in the control of a tyrosine kinase network mediating resistance to nilotinib treatment in CML cells. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.